Local wisdom values assessment on Naik Dango ceremony: Kanayatn Dayaknese society at saham village on civic culture of the people in Indonesia - Mohd Khairul Amri, Kamarudin; Pitalis Mawardi, Baging; Mohd Hanif, Abdullah (2019)
The association among culture and human are interrelated aspect in socio-cultural life. The beliefs of local wisdom Naik Dango ceremony as civic at Kanayatn Dayaknese in Saham Village, Sengah Temila District. This beliefs as divinity values between human and their relationship with God. The role of stakeholders to conserve and preserve the ceremony of Naik Dango as the people culture, cultural resiliency depends on society interest or love for the surrounding culture. Respecting nature properly accordance with the principles of rituals. Family values should be retained in order to reinforce family harmony can be seen in Mutual Cooperation. The cultures that were passed on to the generations as cultural heritage of the indigenous people. The aim of this study to determine the beliefs of local wisdom and the value of divinity human relationship with God in Naik Dango Ceremony. The study indicated that men communities, who always try to search for God and respect Him. The appreciation the surrounding environment, preserving it and make use of it with good ways